Implementasi Program Perilaku Hidup Bersih dan Sehat Rumah Tangga Di Kabupaten Bandung - Nurul Aisyah Dien Rachmani Putri (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2021)
The embodiment of maintaining and improving health status is the declaration of a clean and healthy lifestyle policy which is then shortened to PHBS. According to the Decree of the Minister of Health of the Republic of Indonesia No. 2269/MENKES/PER/XI/2011, PHBS is a set of attitudes carried out based on an understanding of learning outcomes to create independent individuals, families, and communities in the health sector and act actively in creating a healthy society. The main problem in this study is that the percentage of household PHBS program implementation in the Pameungpeuk Health Center working area only reached 24%, quite far from the 2014 Ministry of Health Strategic Plan target, which is 70% of households that have practiced PHBS. as well as the factors supporting and inhibiting the implementation of the PHBS program in household arrangements at the Pameungeuk Health Center. The method used is descriptive qualitative with interview, observation, and documentation studies. While checking the validity of the data using data source triangulation techniques. The author found that the implementation of the household PHBS program at the Pameungpeuk Health Center was carried out through the following processes (i) the logic of the policy, (ii) the environment in which the policy was operationalized, and (iii) the ability of the policy implementer. The results showed that the implementation of the household PHBS program in the work area of the Pameungpeuk Health Center was still not optimal and several obstacles were found in its implementation, namely the lack of human resources, incomplete facilities and infrastructure, lack of training for health promotion officers, and low community support in assisting implementation. this program.